Waste Infrastructure Planning in Tanjung Balai City - Iskandar Zulkarnaen; Abdi Sugiarto (Journal of Information Technology, computer science and Electrical Engineering, 2024)
This study aims to examine Waste Infrastructure Planning in Tanjung Balai City. This qualitative research method, a study of waste infrastructure planning in Tanjung Balai City can provide a deep understanding of the conditions and obstacles faced. This qualitative approach allows researchers to identify solutions that are relevant to local conditions based on the perspectives of stakeholders and the community. The results of the research Recommendations for improvement include increasing the capacity of the landfill, adding a waste transportation fleet, and implementing a waste separation system from the source. The government also needs to establish firm policies and regulations and encourage private sector participation through mutually beneficial partnerships. Overall, waste infrastructure planning in Tanjung Balai City requires full support from various parties, including the government, the community, and the private sector. The suggested steps are expected to create a sustainable and environmentally friendly waste management system, thereby improving the quality of life of the people of Tanjung Balai and maintaining the cleanliness of the city's environment.